2005
DOI: 10.1159/000082435
|View full text |Cite
|
Sign up to set email alerts
|

Hemivertebra: Prenatal Diagnosis, Incidence and Characteristics

Abstract: Objective: Hemivertebra is a rare congenital spinal anomaly where only one side of the vertebral body develops, resulting in deformation of the spine, such as scoliosis, lordosis, or kyphosis. We aimed to determine the incidence and clinical characteristics of hemivertebra. Patients and Methods: We present three fetuses with a prenatal ultrasonographic diagnosis of hemivertebra at 15–22 weeks’ gestation, and we determine the incidence and clinical characteristics of hemivertebra among 78,500 live-born infants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
125
2
4

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(135 citation statements)
references
References 28 publications
4
125
2
4
Order By: Relevance
“…The mean birth weight was 2335 ± 998 g, whereas 4 neonates (28.6%) were growth restricted (<10th percentile). 4 The frequency of growth restriction was not significantly different in fetuses with ( Ventriculomegaly (2) Encephalocele (1) Hydromyelia (1) Other (n = 2) 2-vessel cord (2) cases with nonisolated hemivertebrae were performed for 1 set of twins with a nonreassuring fetal heart rate pattern and 1 instance of type I maternal osteogenesis imperfecta. …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The mean birth weight was 2335 ± 998 g, whereas 4 neonates (28.6%) were growth restricted (<10th percentile). 4 The frequency of growth restriction was not significantly different in fetuses with ( Ventriculomegaly (2) Encephalocele (1) Hydromyelia (1) Other (n = 2) 2-vessel cord (2) cases with nonisolated hemivertebrae were performed for 1 set of twins with a nonreassuring fetal heart rate pattern and 1 instance of type I maternal osteogenesis imperfecta. …”
Section: Resultsmentioning
confidence: 99%
“…1,3 Hemivertebrae are nonisolated in 88.5% of neonates when newborn physical features detected by a geneticist's physical examination are additionally considered. 2 The cardiovascular, urinary, skeletal, gastrointestinal, and central nervous systems are most commonly involved. [1][2][3] Importantly, these birth defects may occur as part of syndromes that may negatively affect the prognosis, such as VATER syndrome (vertebral anomalies, imperforate anus, tracheoesophageal fistula, and renal anomalies), VACTERL syndrome (VATER with cardiac and limb anomalies), Klippel-Feil syndrome, Jarcho-Levin syndrome, OEIS (omphalocele, bladder exstrophy, imperforate anus, and spine anomalies), the Potter sequence, and open spina bifida.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…anomaly; however, according to a recent report by Goldstein et al [1], based on prenatal ultrasound diagnosis, the incidence of hemivertebra is 0.33 out of 1,000 live born infants. The natural history of hemivertebra is well known [2][3][4][5] and if untreated, the deformity will most likely increase throughout childhood and adolescence resulting in structural changes also in the unaffected region of the spine.…”
mentioning
confidence: 99%
“…4 Despite the relevance of diagnosing this condition prenatally, few articles published in the literature have addressed the sonographic criteria for proper diagnosis. [5][6][7] In a recent study, it was shown that most fetuses with a diagnosis of hemivertebrae have associated abnormalities that are frequently syndromes, and these affect their postnatal prognosis. 4 Hence, it is important to achieve a proper prenatal diagnosis.…”
mentioning
confidence: 99%